PENGARUH MOBILE APP FEATURES DI SURABAYA TERHADAP POST-ADOPTION BEHAVIOUR - Alexander Jonathan; Indarini Indarini; Silvia Margaretha (Perpustakaan Universitas Surabaya, 2018)
Abstract - The purpose of this study is to investigate the perception of Mobile App users to thecharacteristics of Mobile App (Mobile App Features) at Surabaya and its impact to Mobile AppUsefulness, Playful Engangement, Mobile App Stickiness, and Mobile App Word of Mouth. This studyanalyzed using Structural Equation Model via the Statistical Package for Social Science computerprogram version 18 and Lisrel 8.70. 180 respondent were drawn from Mobile App users domiciled inSurabaya area. Result of this Study found Mobile App Usefulness have positive and significant impacton Mobile App Stickiness, and Mobile App Word of Mouth, while Playful Engangement only havepositive and significant impact on Mobile App Stickiness.